Carbon and Nitrogen Management in Mangrove Ecosystems in Reducing Greenhouse Gas Emissions: Ecological and Islamic Perspective - Mubaraq, Alfian; Aznawi, Andi Aznan; Basyuni, Mohammad; Sivaipram, Itchika (Islamic Research, 2024)
Mangrove ecosystems, located along tropical and subtropical coastal areas, play a vital role in carbon storage and the nitrogen cycle, both of which significantly influence greenhouse gas emissions. These ecosystems store atmospheric CO₂ in their biomass and sediments. However, widespread mangrove degradation disrupts their ecological functions and environmental stability. This study aims to examine the relationship between carbon and nitrogen cycling in mangrove ecosystems and explore sustainable management strategies to reduce greenhouse gas emissions, integrating ecological perspectives and Islamic ethics. The research employs a comprehensive review of existing studies to analyze the roles of mangroves in carbon sequestration, nitrogen cycling, and their degradation's impacts on greenhouse gas emissions. It also discusses the integration of Islamic principles into mangrove conservation. Findings indicate that mangroves significantly contribute to carbon storage and nitrogen cycle regulation. Mangrove degradation affects their carbon sequestration capabilities, alters environmental conditions, and disrupts microorganisms essential for the nitrogen cycle. Furthermore, incorporating Islamic ethics into mangrove management can strengthen conservation efforts by fostering a sense of responsibility and sustainability. This study highlights the ecological importance of mangrove ecosystems in mitigating climate change through carbon and nitrogen management. It underscores the need for integrating Islamic ethical principles in conservation strategies to enhance sustainable environmental management. Preserving mangroves is critical for reducing greenhouse gas emissions and promoting climate resilience.